The Association Between the Regular Use of Preventive Labor Induction and Improved Term Birth Outcomes: Findings of a Systematic Review and Meta-Analysis. Issue 1 (March 2016) - Nicholson, J.M.; Kellar, L.C.; Henning, G.F.; Waheed, A.; Colon-Gonzalez, M.; Ural, S.
Abstract : ( BJOG . 2015;122(6):773–784) The rate of labor induction in the United States increased from 9.5% to 23.4% between 1990 and 2010, and the rate of cesarean delivery (CD) rose from 23% to 32.9% over the same period. During that time, many observational studies reported associations between induction of labor (IOL) and both CD and neonatal intensive care unit (NICU admission).